Wybrane problemy szacowania wartości kadry (kapitału ludzkiego) - Zarzecki, Dariusz (Selected Problems of Estimating Value of An Assembled Workforce (Human Capital), 2008)
An assembled workforce is an element of intangible assets. Typically an assembled workforce is valued through a cost approach based upon the cost to recruit and the cost to assimilate the workforce. Theoretically the compensation of an employee is at the market rate but there is a benefit in that the workforce is assembled and organized. The paper deals with the key issues related to the assembled workforce valuation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 631-637